RETRACTED: Specific thyroid status and iode supply in pregnant women in Yakutsk city and rural locations - Borisova N.V.; Malogulova I.Sh. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001